Development of a quaternary ammonium poly (amidoamine) dendrimer-based drug carrier for the solubility enhancement and sustained release of furosemide - Murugan, E.; Yogaraj, V. (Frontiers in Chemistry, 2023)
Furosemide (FRSD) is a loop diuretic drug belonging to class IV in biopharmaceutical classification system (BCS) used in the treatment of congestive heart failure and edema. Due to low solubility and permeability, its oral bioavailability is very less. In this study, two types of poly (amidoamine) dendrimer-based drug carriers (generation G2 & G3) were synthesized to increase the bioavailability by solubility enhancement and sustained release of drug. The developed dendrimers enhanced the solubility of FRSD to the tune of 58 & 109-fold respectively compared to pure FRSD. From in vitro studies it is verified that the maximum time taken to release 95 % of drug from G2 & G3 was 420 & 510 min respectively but for pure FRSD only 90 min. such a delayed release is strong evidence for sustained drug release. The cytotoxicity results with Vero and HBL 100 cell line through MTT assay reveals increased cell viability indicating the reduced cytotoxicity and improved bioavailability. Therefore, the present dendrimer-based drug carriers are proved to be prominent, benign, biocompatible and efficient for poorly soluble drugs like FRSD. Hence, they could be convenient choices for real time applications of drug delivery.